Preparations to be together for an unknown period of time - Keresztes, Gábor (Trigon-Film, 2022)
"40 year old Marta has found the love of her life. She met the mysterious János at a medical congress in New Jersey and arranged to meet him again in Budapest. Never before has she felt such strong feelings for someone. After almost 20 years, she now returns to her homeland in Hungary, leaving her brilliant career as a neurosurgeon and her previous life in the USA behind with the hope of a new, more fulfilling existence. As agreed with János, Márta waits on the Freedom Bridge - in vain." [trigon-film.org]
Original: Ungarn 2020
Bonus: Trailer
Bildformat 1.85:1 (16:9)
Keywords: Film; DVD-Video